Understanding the Impacts of Time in Care on Educational Attainment in England - Zhang, Xiaohui (International Journal of Population Data Science, 2025)
Objectives This study captured a broad picture of factors influencing the educational attainment at GCSE and advanced level in England. It examined the causal link between being in care and educational attainment. In particular, this study identified the factors of care experience that may influence looked after children’s educational attainment. Method We used linked administrative data from the Growing Up in England (GUiE) study to examine the impact of time in care on two types of educational attainment: (1) the total number of full GCSE A-C qualifications and (2) the total number of advanced qualifications. We conducted a range of regression analyses to estimate the causal impact of time in care on educational outcomes. We also applied a decomposition method to assess the extent to which observed child characteristics and family background factors explain the attainment gap between children in care and those not in care. Results We found that children with care experience attained significantly fewer full GCSE A–C qualifications and advanced qualifications compared to their peers without care experience. For looked-after children, staying longer in care may lead to better educational attainment. Children who entered care due to parental illness or disability are likely to attain more GCSE full A to C qualifications than those who entered care due to abuse or neglect. On the other hand, children in care due to socially unacceptable behavior may attain fewer qualifications. We also found that about 84% of the gap in GCSE qualifications and 65% of the gap in advanced level qualifications between children in care and those not in care can be explained by the observed factors. Conclusion A large portion of the gap in GCSE and advanced-level qualifications between children in care and those not in care can be explained by observed characteristics. These findings offer valuable insights for policymakers and practitioners to design care systems with proactive strategies that support looked-after children in achieving academic success.